Chapter Teaching design of technologies for mediating collaborative interaction - an emerging pedagogical framework - Baykal, Gökçe Elif; Eriksson, Eva; Ruijten, Peter; Torgersson, Olof (Academia Press, 2023)
Industrial / commercial art & design